Biodiversity, substrate relationship and distribution of Lichens from Telangana and Andhra Pradesh, India - and D. NAGARAJU, C. MANOHARACHARY* (Indian Phytopathology, 2017)
Lichens are one of the important most viable and successful alliances of photobiont and Mycobiont in nature. Lichens exist in three different growth forms and are distributed throughout the world including in Polar Regions. There is little or no information on lichen floristics, their distribution and substrate relationship from Telangana and Andhra Pradesh states. The survey (2010-13) of different forest localities resulted in the collection of 65 Lichens which have been identified upto species level. The data pertaining to their substrate relationships, growth forms and distribution has been presented.